The Song of songs and the fashioning of identity in early Latin Christianity - Shuve, Karl (Oxford early Christian studies, 2016)
Karl Shuve offers a comprehensive analysis of the interpretation of the 'Song of Songs' in the Latin-speaking churches of late antiquity, showing how it was used by bishops and theologians to illuminate complex problems of identity in relation to liturgical practice, doctrinal definitions, and ideas about the body and sexuality.